Pengaruh Kebijakan Manajemen Keuangan Dan Inflasi Terhadap Kinerja Keuangan Pada Pt. Bank Tabungan Negara (Persero) Tbk - Izzati, Nur Izzati; Saroni, Wahid Hasim Saroni; Hendraliany, Srie Hendraliany; Putri, Suci Nadiya Putri (DFAME Digital Financial Accounting Management Economics Journal, 2025)
Since the covid pandemic in 2019, the global economic conditions have experienced significant pressure such as decreased economic activity, as well as disruption of cash flow and liquidity. The impact of the pandemic pressure is felt mainly by the banking industry. However, based on OJK data at the end of 2020, conventional commercial banks with total assets of IDR 8,386 and based on Bank Indonesia, it can be seen that the amount of DPK has increased to IDR 6,665,390 billion in December 2020. Therefore, it is necessary to conduct a profitability ratio analysis that supports financial performance which is proxied by Net Interest Margin (NIM) by testing other financial variables that are indicated to be control variables such as Loan to Deposit Ratio (LDR) and Inflation. This study aims to understand the effect of Loan to Deposit Ratio (LDR) partially on Net Interest Margin (NIM) and see the effect of inflation partially on 1Net Interest Margin (NIM) and understand the simultaneous effect of Loan to Deposit Ratio (LDR) and inflation on Net Interest Margin (NIM) at PT. Bank Tabungan Negara (Persero) Tbk. The research method used is descriptive statistical analysis with a quantitative approach. The data used is secondary data. Testing of research variables was conducted using multiple linear regression analysis method, t-test, F-test, and coefficient of determination (R2) test. Based on the calculation results using SPSS 29.0.1, it was concluded that the hypothesis that the Loan to Deposit Ratio (LDR) and Inflation simultaneously have a significant effect on Net Interest Margin (NIM) Ha is accepted, Ho is rejected. However, partially (t-test) the Loan to Deposit Ratio (LDR) does not have a significant effect on Net Interest Margin (NIM) while Inflation has a significant effect on Net Interest Margin (NIM).